Peningkatan Proses Pembelajaran Tematik Terpadu dengan Menggunakan Model Problem Based Learning di Kelas IV SD - Mahendra, Ade; Mansurdin, Mansurdin (Universitas Negeri Padang, 2021)
The purpose of this research is to describe an integrated thematic learning process improvement to the model of problem based learning in fourth grade elementary school 15 Ampang Gadang Agam. In this study applying the type of PTK research uses qualitative and quantitative approaches. The subject in this study is the teacher (researches) and student of totaling 27 people consisting of 15 male students and 12 female students. Results showed an increase in: a) RPP cycle I with an average of 74.99% (enough) and cycle II 94.44% (very good), B) Implementation on the teacher aspect of cycle I with an average of 85.71% (good) and cycle II 92.85% (very good), while the implementation of the student aspect of the cycle I with an average of 83.92% (good), and cycle II 92.85% (very good), c) The assessment of the learners in the improvement of learning outcomes on the I cycle was obtained with an average of 78.75% and cycle II by an average of 89.01%. Based on the results it can be concluded that with the Problem Based Learning (PBL) model can improve the integrated thematic learning process in grade IV.